2008
DOI: 10.1007/s10450-008-9124-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of volatile hydrocarbons on natural zeolite-clay material

Abstract: This study investigated the vapor-phase sorption of hydrocarbons (HC) of various chemical nature (n-hexane, iso-octane, benzene, toluene and p-xylene) on zeolite-clay material (ZCM) of Tatarsky-Shatrashansky deposit (Tatarstan, Russia). For comparison, we also studied HC sorption on natural high-grade zeolite (Z) of St. Cloud Mine (New Mexico, USA), two local bentonite clays and synthetic zeolite-molecular sieve Ms5A. As a result, sorption capacity of ZCM towards aliphatic and aromatic HC was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The values of bulk density, true density, and porosity of the particle are shown in Table . The porosity can be considered low if compared with other clays, as studies by Breus et al showed particle porosity of 51 %.…”
Section: Resultsmentioning
confidence: 99%
“…The values of bulk density, true density, and porosity of the particle are shown in Table . The porosity can be considered low if compared with other clays, as studies by Breus et al showed particle porosity of 51 %.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior can be explained by the presence of the salt used in the organofilization process, which can occupy the active sites that would be available for the nitrogen. The porosity of the organoclay can also be considered low when compared to other materials, and its increase after the process may be due to the drag of the clay lamellas (He et al 2006;Breus et al 2008;Antonelli et al 2021). a Specific surface area by BET method; b volume of micropore (Eq.…”
Section: 2amentioning
confidence: 99%